Oleiculture : Caracterisation De Six Varietes D’olives Introduites Dans Le Sud – Est Algerien - Abdelaziz, Benaziza; Djamila, Semad (European Scientific Journal, ESJ, 2016)
The cultivation of olive trees in the pre-Saharan areas of Algeria showed yields that are satisfactory and has acceptable values of oil quality. In the context of improvement of culture and order to respond to international norms for a particular exporting oil extra virgin, she should have a lower 0.8% acidity required by the economic operators. For enhanced characterization and valorization some local of olive oil varieties introduced, this work falls under this objective and is articulated primarily on six varieties. It is based essentially on oil quality parameters.